Enhancing Learning Motivation for Dharma Wanita Kindergarten Students in Poko Jambon Ponorogo, Indonesia - Nisa, Yushfa Yufrida Nazzun; Saputri , Wahyu Eka; Putri, Zakiyah Rahmah; Nurdiana, Nurdiana; Khoirurrosyidin, Khoirurrosyidin (Jurnal Inovasi dan Pengembangan Hasil Pengabdian Masyarakat, 2024)
This study aims to increase the learning motivation of Dharma Wanita Kindergarten students in Poko, Jambon, and Ponorogo, through an educational assistance program. This activity was conducted with a mentoring and counseling approach, using participatory observation and in-depth interview data collection techniques. This program includes various specific activities such as educational games, storytelling sessions, social skills training, and art and creativity activities designed to increase students' interest and participation in learning. The methods applied involve direct observation of student behavior and attendance and interviews with teachers and parents to obtain a comprehensive picture of the changes that have occurred. The results of this activity showed a significant increase in learning motivation, as indicated by an increase in students' daily attendance by 25%, active participation in class by 30%, and an increase in learning evaluation results by 20%. These data were analyzed qualitatively and quantitatively to ensure the validity of the research results. This study concludes that this educational mentoring program has succeeded in creating a fun and productive learning environment, and significantly increased students' learning motivation at Dharma Wanita Poko Kindergarten. With these results, it is hoped that this program can be adopted and implemented in other educational institutions to achieve similar results.